MENINGKATKAN HASIL BELAJAR SISWA KELAS X IIS MENGGUNAKAN METODE PROBLEM BASED LEARNING - Bota, Scolastika (JAPB: Jurnal Agama, Pendidikan dan Budaya, 2026)
This study aims to determine the improvement of learning outcomes of class X IIS students on the history of ancient Israel using the problem-based learning method at SMAK Santa Maria Immaculata-Adonara. This research is a classroom action research consisting of planning, implementation, observation, and reflection. The subjects in this study were 18 class XII S students. Data collection techniques used observation and documentation. The results of the study stated that the application of the Problem Based Learning (PBL) method in contextual learning had a positive impact on student outcomes, which was indicated by an increase in the average class value of each cycle, namely cycle I 74.88% and cycle II 83.83%. This proves that through the application of the Problem Based Learning (PBL) method, learning outcomes of class X IIS students at SMAK Santa Maria Immaculata Adonara can be improved.